CONCENTRATE SUBSTITUTION WITH THE BY-PRODUCT OF MEAL WORM (Tenebrio Molitor) ON FEEED CONVERSION AND OVER FEED COST OF RABBITS - Hendrikus Nango Rema, Tri Ida Wahyu Kustyorini, Dyah Lestari Yulianti (Jurnal Sains Peternakan, 2016)
ABSRACT This study to determine the Substitution ofconcentrate with by-product of Meal wornm on feed conversion and Income Over Feed Cost (IOFC) of rabbits. The material used in this study were 12 rabbits aged to months with an average initial weight is 0,5 kg. Basal feed given is forage, water spinachand concentrates. Forage given as much as 40% and the rest is concentrates. Treatment research is the substitution of concentrate with the by-product of Meal worm as muchas 0% (P0), 33,3% (P1), 66,7% (P2), and 100% (P3). The research method was an experiment with a randomized block design, 4 treatment three replication. The research variabels are feed conversion abd IOFC (Rp/head). The research data were tabulated and analyzed using analsysis of variance, if there is a difference than continued by Honestly Significat Difference (HSD). The results of data analysis showed no difference (P>0.05) with substitution of concentrate with the by-product of Meal worm on feed conversion and IOFC of rabbit rearing. Average feed conversion op P0,P1,P2,and P3 were : 7.22; 5.91; 7.91; and 11.83 respectively. While the average IOFC (Rp/head) for P0,P1,P2, and P3 were: 1,960; 4,936; 6,691; and 3.361 respectively. The substitution of concentrate with 33,3% of the by-product of Meal worm can be applied in rabbits rearing. Based on the results of research in sampulkan that substitution Meal worm waste with prosetase 20% give the best feed conversion and substitution as much as 40% gave the highest value of IOFC, Based on the research results obtained, it is advised to use the substitution of concentrate with Meal waste as much as 20%. Keywords: Meal worm, Feed Conversion,Income Over Feed Cost , rabbit